1978
DOI: 10.1126/science.200.4343.759
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ammonium Cyanate and Urea by Reduction of Nitric Oxide on Platinum, Rhodium, and Ruthenium Catalysts

Abstract: Nearly quantitative conversion of nitric oxide (NO) into N(2)H(4)CO has been obtained in the reduction of NO with carbon monoxide and hydrogen over platinum and rhodium catalysts. Depending on the temperature of collection, N(2)H(4)CO is isolated as ammonium cyanate or its isomer, urea. The process is an effective way of recovering fixed nitrogen from dilute industrial streams containing NO. Ammonium cyanate may play a role in the reduction of NO in automotive exhaust control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In auto exhaust, NH 3 can be formed by the direct reaction of NO with H 2 , via the hydrolysis of an isocyanate intermediate, or by the direct reaction of NO with hydrogen produced via a water−gas shift reaction (WGSR) . In a study of the reduction of NO with a mixture of CO and H 2 in the presence of H 2 O and O 2 over supported Rh and Pt catalysts, Voorhoeve et al reported NH 3 formation via an isocyanate intermediate. By investigating the role of steam reforming and the water−gas shift reaction in the behavior of three-way catalysts, Whittington et al found that both reactions become important only at temperatures higher than those needed to facilitate oxidation (i.e., only when the monolithic catalyst bed is depleted of oxygen).…”
Section: Discussionmentioning
confidence: 99%
“…In auto exhaust, NH 3 can be formed by the direct reaction of NO with H 2 , via the hydrolysis of an isocyanate intermediate, or by the direct reaction of NO with hydrogen produced via a water−gas shift reaction (WGSR) . In a study of the reduction of NO with a mixture of CO and H 2 in the presence of H 2 O and O 2 over supported Rh and Pt catalysts, Voorhoeve et al reported NH 3 formation via an isocyanate intermediate. By investigating the role of steam reforming and the water−gas shift reaction in the behavior of three-way catalysts, Whittington et al found that both reactions become important only at temperatures higher than those needed to facilitate oxidation (i.e., only when the monolithic catalyst bed is depleted of oxygen).…”
Section: Discussionmentioning
confidence: 99%
“…It is useful to compare this process for the production of urea with an alternative that is based on the use of ruthenium as a catalyst. 35 In either case, the acceptability score ranked second overall. This is due to unfavourable CO 2 emissions by these processes.…”
Section: Ureamentioning
confidence: 98%
“…On the other hand, the H 2 oxidation without CO, CO 2 , and H 2 O was rapidly suppressed (Figure 5a). Since it has been reported that NO reduction by CO was faster at low temperature (<270 °C) than that by H 2 , 25,33 NO was probably reduced to N 2 O and/or N 2 by CO. Tamaru et al reported that the NO reduction by H 2 was significantly suppressed by adsorbed oxygen, 28 which was consistent with our result that the H 2 oxidation was depressed by nitrosyls (Figure 5a) in contrast to the rapid reduction of nitrosyls under a reduction atmosphere. Compared with the rapid deactivation for the PROX in the presence of CO 2 and H 2 O (Figure 3b, 150 °C), the absence of H 2 O enhanced the activity for both CO and H 2 oxidation, which made most of the catalyst bed reductive and kept the catalyst active (Figure 5b).…”
Section: In-situ Ir Measurementsmentioning
confidence: 98%
“…Voorhoeve et al studied the reduction of NO over various Ru catalysts in a gas composition of 0.13 vol % CO, 0.4 vol % H 2 , 1.3 vol % CO, 3 vol % H 2 O, and 3 vol % CO 2 balanced with He at 150-500 °C. 33 They reported that N 2 O, N 2 , and NH 3 were exhausted at 150-200 °C. Thus N 2 O and N 2 was probably formed under a reduction atmosphere (Figure 9(6, 7), in addition to the NH 3 formation by the hydrolysis of isocyanates (Figure 9(2)).…”
Section: In-situ Ir Measurementsmentioning
confidence: 99%
See 1 more Smart Citation